Growth and reduction of cost of production of Pangasius hypophthalmus (Sauvage, 1878) with alternate feeding schedules - Ali, M Z; Haque, M K I; Parveen, R; Hussain, M G; Mazid, M A (Indian Journal of Fisheries, 2011)
A feeding trial was conducted in pond condition to investigate the effect of alternate feeding schedules on the growth and production cost of Thai pangas, Pangasius hypophthalmus. Ten experimental ponds each of 400 m2 size were divided into 5 treatment groups each with two replicates. Fish (5.3 + 0.6 g average weight) were stocked at the rate of 1,000 per pond (25,000/ha). High protein (30%, H) and low protein (15%, L) diets were prepared using locally available ingredients. Five different feeding schedules employed were: high protein diet (30% protein, H, low protein (15% protein, L) diet, 1 day low protein diet followed by 1 day high protein diet (1L/1H), 2 days low protein diet followed by 2 days high protein diet (2L/2H) and 7 days low protein diet followed by 7 days high protein diet (7L/7H). The fish were fed twice daily at the rate of 15, 10, 8 and 5% of their body weight for the 1st, 2nd, 3rd and 5th months respectively. Significantly (P<0.05) higher growth rate of Thai pangas were achieved in feeding schedules of H, 1L/1H and 2L/2H, and the lowest with 7L/7H. The FCR values ranged between 2.08 to 2.79 with H and 1L/1H showing significantly the best FCR. The production of Thai pangas ranged between 308 to 472 kg/400 m2 pond (7,708 to 11,805 kg/ha/5 months) with 1L/ 1H feeding schedule giving the highest production. A simple economic analysis showed that fish in1L/1H fed alternately with low and high protein diets resulted inthe highest net profit. The results of the study demonstrated the feeding of fish continuously with high protein diet is not economical.